Learning to lament in a South-African township in 2019 : help from Psalms and the Lord’s Prayer - Dickie, June F. (Neotestamentica, 2019)
Distressing situations call for concerted prayer, but in practice traumatised people often battle to express themselves adequately to find release and comfort. Fortunately, the Bible contains prayers that can be used helpfully, in particular the Lord’s Prayer and psalms of lament. In this study, the value of lament prayer is first explored, in both the Old Testament and the New Testament. Then it is noted that lament psalms utilise a basic structure that contemporary sufferers can follow to compose their own lament prayers. The Lord’s Prayer is also helpful in that it calls for the coming of God’s Kingdom and thus provides a way to name injustices and pray for the Lord’s will to be effected. Empirical studies with these two prayer-forms helped participants in a South-African township to express their pain to God. The structure of biblical laments helped them express their own personal pain, and the Lord’s Prayer gave space for them to voice their frustrations against the lack of justice in their situations. In these days of much trauma, this study presents a way in which pain-bearers can learn to release their concerns and feel empowered.
free
Keywords: Empowerment; Lament; Lord’s Prayer; Suffering; Townships; justice